Trends and Patterns of Road Traffic Accidents in Maharashtra: A Comparative Examination of NCRB and MEMS Databases - Biranchi Narayan Jena; Dnyaneshwar Shelke; Shoma Shrivastava (Indian Journal of Community Medicine)
Background: The emergence of high incidence of Road Traffic Accidents (RTA) has contributed to the burden of Non-Communicable Disease (NCD) both in terms of mortality and morbidity. It is very important to have a structured and accurate database for strategizing road safety and associated public health benefits. There are multiple sources of data available for the research of road traffic accidents and road safety. It is utmost necessary to identify the most appropriate data source for RTA research. Materials and Methods: The current study is based on five years’ time series data (2017 to 2021) from two data sources namely National Crime Record Bureau (NCRB) and Maharashtra Emergency Medical Services (MEMS). Injury rate and death rate was used along with the trend analysis to define the trend of RTA. Corelation coefficient was used for establishing the patterns of reporting of RTA in the state of Maharashtra. The data is analysed by using MS Excel and SPSS16.0. Results: Both the databases exhibit a declining trend in the reporting of RTA in the state of Maharashtra with a CAGR of -1.99% in NCRB and -13.77% in MEMS. Although the number of incidents reported in NCRB is around 40% less than MEMS, both the sources have almost the same number of victims per accident (r= 84%). Injury rate reported in NCRB is around 40% less than the MEMS data and the variation in injury rate in cities is high as per NCRB data than in MEMS data. MEMS data provides a number of information including the severity of injury which may be useful for the analysis and insight generation. Conclusion: Both the databases are important in providing crucial information for generating insight and strategies for road safety. A central database in combining both the database would be ideal for the researchers in the areas of injury and road safety. MEMS was the better source in terms of amount of information for epidemiological research in road safety.